2016
DOI: 10.3390/app6100286
|View full text |Cite
|
Sign up to set email alerts
|

Classical Optimization of Cellulase and Xylanase Production by a Marine Streptomyces Species

Abstract: Cellulase and xylanase are in high demand for application in several industrial processes, consequently necessitating the bioprospecting and manipulation of microbes for novel and greater enzyme productivity. This study reports on the optimal conditions for cellulase and xylanase production by a marine bacterial isolate from Nahoon beach sediment, via the classical process of one variable per time. Furthermore, the inducing effect of mono-and polysaccharides on enzyme production was investigated. The 16S rDNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 59 publications
5
21
1
Order By: Relevance
“…In addition, many enzymatic processes and the transport of various components across the cell membrane are strongly affected by the pH of the medium [55]. A optimum pH is required to maintain the three-dimensional shape of the active site of enzymes and the change in pH results in a loss of functional shape of the enzyme due to alterations in the ionic bonding of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many enzymatic processes and the transport of various components across the cell membrane are strongly affected by the pH of the medium [55]. A optimum pH is required to maintain the three-dimensional shape of the active site of enzymes and the change in pH results in a loss of functional shape of the enzyme due to alterations in the ionic bonding of the enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…The parameters for optimal extracellular peroxidase activity were determined as described by Fatokun et al. . Briefly, the various culture parameters were adjusted for optimum peroxidase activity using the conventional method of one factor at a time.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the various culture parameters were adjusted for optimum peroxidase activity using the conventional method of one factor at a time. Then, the determined optimized conditions were used in subsequent fermentation .…”
Section: Methodsmentioning
confidence: 99%
“…NZ produced maximum enzyme titre near the end of the exponential phase and early stationary phase [65]. B. cereus [66] and B. halodurans PPKS-2 [67] showed maximum xylanase production after 48 h. Gupta and Kar [68] studied xylanase production by Bacillus sp. and reported that maximum xylanase production was observed in 48 h and 72 h using wheat bran and corn cob as a substrate, respectively.…”
Section: Resultsmentioning
confidence: 99%